2014
DOI: 10.1002/ejoc.201400090
|View full text |Cite
|
Sign up to set email alerts
|

Selective Suzuki–Miyaura Monocouplings with Symmetrical Dibromoarenes and Aryl Ditriflates for the One‐Pot Synthesis of Unsymmetrical Triaryls

Abstract: A highly selective and efficient method for the monoarylation of symmetric dibromo and ditriflate aryl compounds is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…17 However, many of these approaches are costly and wasteful. Although the monoarylation of unbiased dihaloarenes with certain halide groups through elaborate catalyst design and/or the fine-tuning of reaction parameters such as temperature, solvent, and additives has been reported, [18][19][20][21][22] the exploration of conceptually new and generally applicable strategies to control and improve the monoarylation selectivity remains in high demand. We have previously reported broadly applicable solidstate cross-coupling reactions using mechanochemistry.…”
mentioning
confidence: 99%
“…17 However, many of these approaches are costly and wasteful. Although the monoarylation of unbiased dihaloarenes with certain halide groups through elaborate catalyst design and/or the fine-tuning of reaction parameters such as temperature, solvent, and additives has been reported, [18][19][20][21][22] the exploration of conceptually new and generally applicable strategies to control and improve the monoarylation selectivity remains in high demand. We have previously reported broadly applicable solidstate cross-coupling reactions using mechanochemistry.…”
mentioning
confidence: 99%
“…Higher yields of products containing electron-withdrawing groups probably resulted from an increased reactivity of the monobromo intermediate toward the second cross-coupling reaction. This observation was mentioned by Minard et al [ 59 ] in the course of a one-pot two-step Suzuki cross coupling of 3,5-, 2,6-dibromopyridines and dibromobenzenes with various arylboronic partners of different electronic properties.…”
Section: Resultsmentioning
confidence: 72%
“…The final outcome of such a procedure is governed by many factors, including differences in site reactivity of polyhaloarenes (concerning both regio- and chemoselectivity), reaction conditions (the nature of the palladium/ligand, temperature, base, solvents) and the steric interactions between both cross-coupling partners. Minard et al [ 59 ] pointed out that if an arylboronic acid involved in sequential couplings bears substituents with electron-withdrawing and electron-donating groups, the choice of the order of its introduction may be crucial for the final outcome. Our starting material constitutes a special case where both coupling sites are isoelectronic and equivalent in terms of steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aryl halides, as one kind electrophilic coupling partner, is often utilized for the SM reactions . However, phenol derivatives, such as triflates (OTf), mesylates (OMs) and tosylates (OTs), bearing less expensive and easier to handle nucleofuges, offer an alternative of choice in terms of the electrophilic partner. In 2015, Hanley et al reported that the SM reactions of aryl fluorosulfate and arylboronic acids could be achieved smoothly by using palladium or nickelphosphine catalysts in combination, and a series of biaryls were prepared in good to excellent yields.…”
Section: Introductionmentioning
confidence: 99%